Phosphorus and sodium containing catalyst and its use in hydrodesulfurization processes - Patents.com

JP2024514932A5Pending Publication Date: 2025-04-22IFP ENERGIES NOUVELLES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023564405
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-21
Filing Date
2022-04-15
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing hydrodesulfurization catalysts face challenges in achieving high selectivity for sulfur removal while minimizing the hydrogenation of olefins, leading to significant octane number loss in gasoline fractions.

Method used

A catalyst comprising Group VIB, Group VIII elements, phosphorus, and sodium on an alumina support, with specific molar ratios and concentrations, enhances the selectivity and activity for hydrodesulfurization processes.

Benefits of technology

The catalyst improves the selectivity and activity in hydrodesulfurization, reducing sulfur content without substantial olefin hydrogenation, thus maintaining the octane number of gasoline fractions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A catalyst comprising an active phase based on at least one group VIB metal and at least one group VIII metal, phosphorus, sodium and an alumina-based support, the sodium content of which, relative to the total weight of the catalyst, is 0.01 to 0.05% by weight. 2 0 form, and the phosphorus to sodium molar ratio is 1.5 to 30.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of hydrotreating gasoline fractions, in particular gasoline fractions produced from fluidized bed catalytic cracking units.More particularly, the present invention relates to a catalyst and its use in a process for hydrodesulfurization of sulfur-containing olefinic gasoline fractions, for example gasoline produced from catalytic cracking, which process is required to reduce the content of sulfur-bearing compounds without hydrogenating olefins and aromatic compounds. [Background technology]

[0002] Petroleum refining, and also petrochemistry, is now subject to new constraints, since all countries are gradually adopting strict sulfur specifications, the goal being, for example, to achieve 10 ppm (by weight) of sulfur in market gasoline in Europe and Japan. The problem of reducing the sulfur content is essentially focused on gasoline obtained by cracking, whether catalytic (FCC; Fluid Catalytic Cracking) or non-catalytic (coking, visbreaking, steam cracking), being the main precursor of sulfur in the gasoline pool.

[0003] One solution known to those skilled in the art for reducing the sulfur content consists in carrying out hydrotreating (or hydrodesulfurization) of hydrocarbon fractions (especially catalytic cracking gasoline) in the presence of hydrogen and heterogeneous catalysts. However, this method has the major drawback of a very significant drop in octane number if the catalyst used is not sufficiently selective. This drop in octane number is linked, among other things, to the hydrogenation of olefins present in this type of gasoline, which is carried out simultaneously with hydrodesulfurization. Unlike other hydrotreating methods, hydrodesulfurization of gasoline must therefore be able to meet two contradictory constraints: providing an extreme hydrodesulfurization of gasoline and limiting the hydrogenation of the unsaturated compounds present.

[0004] One approach to address this dual problem consists of using hydrodesulfurization catalysts that are both active for hydrodesulfurization and highly selective for hydrodesulfurization relative to olefin hydrogenation reactions.

[0005] Therefore, patent document 1 discloses a process for the hydrodesulfurization of olefinic gasoline fractions containing sulfur, which is known from the prior art and is carried out in the presence of a catalyst comprising an active phase based on at least one metal of group VIB and at least one metal of group VIII on an alumina-type support, said support further comprising an alkali metal in a content ranging from 0.2 to 3% by weight relative to the support, the support may contain further compounds selected from boron, phosphorus and silicon, the content of which is not disclosed.

[0006] Patent document 2 describes the use in a selective desulfurization process of a catalyst comprising an active phase based on at least one metal of group VIB and at least one metal of group VIII and a support simultaneously comprising 0.5-50% by weight of magnesium and 0.02-10% by weight of an alkali metal, relative to the total weight of the catalyst, however, this document does not disclose the presence of phosphorus in the catalyst.

[0007] Furthermore, US Pat. No. 5,399,633 discloses a method for producing a gasoline fraction in the presence of a catalyst containing one or more metals from cobalt, molybdenum, nickel and tungsten on an alumina-based oxide support and further containing another metal selected from alkali metals, iron, chromium, cobalt, nickel, copper, zinc, yttrium, scandium and lanthanides. The alkali metal is preferably potassium. However, this document does not disclose the presence of phosphorus in the catalyst.

[0008] Patent document 4 discloses a process for hydrogenating a liquid fraction containing unsaturated compounds in the presence of a catalyst comprising a group VIII metal and optionally a group VIB metal deposited on an alumina or silica-alumina type support, promoted by an alkali metal, the alkali metal having a content of 0.1-5% by weight, preferably 0.4-2.5% by weight. However, this document does not disclose the presence of phosphorus in the catalyst.

[0009] Finally, patent application WO 2005 / 023933 discloses a process for hydrodesulfurization of naphtha fractions in the presence of a catalyst, the catalyst comprising an active phase based on a metal of group VIB, preferably molybdenum, a metal of group VIII, preferably cobalt, and a metal of group IA or group IIA, preferably calcium or sodium, more preferentially calcium, with a content of 0.01 to 2% by weight relative to the total weight of the catalyst, and an alumina-based support. However, this document does not disclose the presence of phosphorus in the catalyst.

[0010] Therefore, currently, there remains strong interest among refiners in hydrodesulfurization catalysts, especially those with improved catalytic performance in terms of catalytic activity and / or selectivity in the hydrodesulfurization of gasoline fractions, especially hydrodesulfurization that, once used, is therefore capable of producing low-sulfur gasoline without a serious reduction in octane number.

[0011] In this connection, one of the objects of the present invention is to provide a catalyst for the hydrodesulfurization of sulfur-containing olefinic gasoline cuts and its use in a process therefor, which exhibits performance levels of activity and selectivity that are at least as good as, and even better than, the catalysts known from the prior art. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] European Patent Application Publication No. 0736589 (JP Patent Publication No. 8-277395) [Patent Document 2] U.S. Pat. No. 5,266,188 [Patent Document 3] US Patent Application Publication No. 2010 / 219102 [Patent Document 4] U.S. Pat. No. 3,494,857 [Patent Document 5] US Patent Application Publication No. 2006 / 213814 Summary of the Invention [Means for solving the problem]

[0013] (Subject of the Invention) The subject of the present invention is a catalyst comprising a support comprising at least one group VIB element, at least one group VIII element, phosphorus, sodium and alumina, the sodium content being, relative to the total weight of the catalyst, less than Na 2 The catalyst is in the form of phosphorus and sodium, and the molar ratio between phosphorus and sodium is 1.5 to 300.

[0014] The applicant has surprisingly discovered that the use of a catalyst comprising at least one group VIB element, at least one group VIII element, phosphorus, sodium and a support comprising alumina, with a specific sodium content and a specific molar ratio between sodium and phosphorus, allows, by a synergistic effect, to improve the performance in a process for hydrodesulfurization of olefinic gasoline fractions containing sulfur, more particularly in terms of selectivity. Indeed, without being bound by any theory, the presence of sodium in a well-defined amount in addition to a specific relative composition between sodium and phosphorus in the catalyst induces a modification of the interaction between the surface of the alumina support and the active phase of the catalyst, thus making it possible to improve the performance in the process for hydrodesulfurization of gasoline, particularly in terms of selectivity and activity.

[0015] According to one or more embodiments, the total content of group VIII elements is between 0.5 and 10 wt. %, based on the weight of the oxides of said group VIII elements relative to the total weight of the catalyst.

[0016] According to one or more embodiments, the content of group VIB element is between 1 and 30 wt. %, based on the weight of the oxide of said group VIB element relative to the total weight of the catalyst.

[0017] According to one or more embodiments, the phosphorus content is expressed as P relative to the total weight of the catalyst. 2 O 5 The weight of the component is 0.1 to 10% by weight.

[0018] According to one or more embodiments, the molar ratio between the group VIII element and the group VIB element is between 0.1 and 0.8.

[0019] According to one or more embodiments, the molar ratio between the Group VIII element and sodium is between 2 and 400, calculated based on the Group VIII element content and the sodium content relative to the total weight of the catalyst.

[0020] According to one or more embodiments, the molar ratio between the group VIB element and the sodium is between 5 and 500, calculated based on the content of the group VIB element and the sodium content relative to the total weight of the catalyst.

[0021] According to one or more embodiments, the molar ratio between phosphorus and the group VIB element is between 0.2 and 0.35.

[0022] According to one or more embodiments, the phosphorus content is expressed as P relative to the total weight of the catalyst. 2 O 5 The weight of the mixture is 0.3 to 5% by weight.

[0023] According to one or more embodiments, the molar ratio between phosphorus and sodium is between 2 and 100, calculated based on the elemental phosphorus content and the elemental sodium content relative to the total weight of the catalyst.

[0024] In one or more embodiments, the Group VIII element is cobalt and the Group VIB element is molybdenum.

[0025] According to one or more embodiments, the specific surface area of ​​the catalyst is 50 to 200 m 2 / g.

[0026] According to one or more embodiments, the pore volume of the catalyst is less than 0.5 cm 3 / g~1.3cm 3 / g.

[0027] Another subject of the invention relates to a process for hydrodesulfurization of a sulfur-containing olefinic gasoline fraction, in which the gasoline fraction, hydrogen and the catalyst according to the invention are contacted, the temperature at which the hydrodesulfurization process is carried out is between 200 ° C and 400 ° C, the total pressure is between 1 and 3 MPa, the hourly space velocity is defined as the volumetric flow rate of the feed relative to the volume of the catalyst, and the hydrodesulfurization process is carried out at a temperature of between 200 ° C and 400 ° C, the total pressure is between 1 and 3 MPa, and the hourly space velocity is defined as the volumetric flow rate of the feed relative to the volume of the catalyst, -1 ~10h -1 and the volume ratio of hydrogen / gasoline fraction is 100-600 SL / L.

[0028] According to one or more embodiments, the gasoline is gasoline produced from a catalytic cracking unit. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Detailed Description of the Invention (1.Definition) The groups of chemical elements are then given according to the CAS classification (CRC Handbook of Chemistry and Physics, published by CRC Press, editor in chief DR Lide, 81st edition, 2000-2001). For example, group VIII according to the CAS classification corresponds to the metals in columns 8, 9 and 10 according to the new IUPAC classification.

[0030] The BET specific surface area is determined by nitrogen physical adsorption according to standard ASTM D3663-03, the method described in the monograph by Rouquerol F., Rouquerol J. and Singh K. “Adsorption by Powders & Porous Solids: Principles, Methodology and Applications”, Academic Press, 1999.

[0031] The total pore volume is measured by mercury porosimetry according to standard D4284-92 with a wetting angle of 140°, for example using an Autopore® III model device of the Micromeritics® brand.

[0032] The content of elements of groups VIII, VIB and V is measured by X-ray fluorescence and inductively coupled plasma (ICP) spectroscopy for sodium.

[0033] (2. Description) (catalyst) The catalyst according to the present invention comprises at least one Group VIB element, at least one Group VIII element, phosphorus, sodium, and a support comprising alumina, the sodium content being Na 2 The molar ratio between phosphorus and sodium, calculated based on the phosphorus content and the sodium content, relative to the total weight of the catalyst, is 1.5 to 300.

[0034] The catalyst according to the present invention is Na 2 The catalyst contains from 50 to 2000 ppm by weight, preferably from 100 to 1500 ppm by weight, more preferentially from 100 to 1000 ppm by weight, more preferentially from 150 to 950 ppm by weight of sodium, measured in the form of O oxide, relative to the total weight of the catalyst.

[0035] The group VIB elements are preferentially selected from molybdenum and tungsten, more preferentially from molybdenum.The group VIII elements are preferentially selected from cobalt, nickel and a mixture of these two elements, more preferentially from cobalt.

[0036] The total content of group VIII elements is generally between 0.5 and 10% by weight of group VIII oxide relative to the total weight of the catalyst, preferably between 0.8 and 9% by weight of group VIII oxide relative to the total weight of the catalyst, highly preferably between 0.9 and 6% by weight. When the element is cobalt or nickel, the element content is expressed as CoO or NiO, respectively.

[0037] The content of the group VIB element is generally 1-30% by weight of the oxide of the group VIB element relative to the total weight of the catalyst, preferably 2-20% by weight of the oxide of the group VIB element relative to the total weight of the catalyst, and highly preferably 4-15% by weight. When the element is molybdenum or tungsten, the metal content is MoO 3 or WO 3 It is expressed as:

[0038] The contents of Group VIB, Group VIII, phosphorus and sodium in the catalysts are expressed as oxides after correction for the loss on ignition of the catalyst samples at 550°C for 2 hours in a muffle furnace. The loss on ignition is due to the loss of moisture. It is determined according to ASTM D7348.

[0039] The phosphorus content is the percentage of P relative to the total weight of the catalyst. 2 O 5Preferably 0.1 to 10% by weight of P relative to the total weight of the catalyst. 2 O 5 The content is preferably 0.3 to 5% by weight, and more preferably 0.5 to 3% by weight.

[0040] The molar ratio between phosphorus and sodium in the catalyst is between 1.5 and 300, preferably between 2 and 100, highly preferably between 3 and 80 and more preferentially between 4 and 60.

[0041] The molar ratio between the group VIII element and sodium in the catalyst is advantageously between 2 and 400, preferably between 2 and 300, highly preferably between 3 and 250. The molar ratio is calculated based on the content of the group VIII element and the Na content relative to the total weight of the catalyst.

[0042] The molar ratio between the group VIB element and sodium in the catalyst is advantageously between 5 and 500, preferably between 5 and 400, highly preferably between 5 and 250. The molar ratio is calculated based on the group VIB element content and the Na content relative to the total weight of the catalyst.

[0043] Preferably, the molar ratio between the group VIII element and the group VIB element of the catalyst is between 0.1 and 0.8, preferably between 0.2 and 0.6, preferably between 0.3 and 0.5, even more preferably between 0.35 and 0.45.

[0044] Preferably, the molar ratio between phosphorus and the group VIB element is between 0.2 and 0.35, preferably between 0.23 and 0.35, even more preferably between 0.25 and 0.35.

[0045] The specific surface area of ​​a catalyst is generally 50 to 200 m 2 / g, preferably 60 to 190 m 2 / g, preferably 60 to 170m 2 / g.

[0046] The pore volume of the catalyst is generally 0.5 cm 3 / g~1.3cm 3 / g, preferably 0.6 cm 3 / g~1.1cm3 / g.

[0047] (Alumina support) The support of the catalyst according to the invention comprises alumina, preferably the support consists of alumina.

[0048] In one embodiment according to the invention, the presence of sodium in the catalyst is due to the presence of sodium in the support. In this embodiment, the sodium content is calculated by the weight of sodium and its Na 2 Measured in the form of O oxide, it is preferably between 50 and 2500 ppm by weight, preferably between 50 and 2000 ppm by weight, and even more preferentially between 100 and 1500 ppm by weight, relative to the total weight of the support.

[0049] The pore volume of the support is generally 0.5 cm 3 / g~1.3cm 3 / g, preferably 0.65 cm 3 / g~1.2cm 3 / g.

[0050] The specific surface area of ​​the carrier is generally 50 to 200 m 2 / g, preferably 60 to 190 m 2 / g.

[0051] The carriers can be in the form of balls, extrudates of any geometric shape, powders, platelets, pellets, compressed cylinders, ground solids or any other shaped form.Preferably, the carriers are in the form of beads with a diameter of 0.5-6 mm or in the form of cylindrical, trilobal or tetralobal extrudates with a circumscribed circle diameter of 0.8-3 mm.

[0052] The support of the catalyst according to the invention can be synthesized by various methods known to those skilled in the art, for example, aluminum trihydroxide (Al(OH) 3) type precursor (also known as hydrargillite or gibbsite), which is for example from the method commonly called "Bayer". Shaping is then carried out, for example by granulation, followed by hydrothermal treatment and finally calcination, which leads to obtaining alumina. This method is described in detail, among others, in the publication Alumina, in Handbook of Porous Solids, edited by F. Schuth, KSW Sing and J. Weitkamp, ​​Wiley-VCH, Weinheim, Germany, 2002, pp. 1591-1677 by P. Euzen, P. Raybaud, X. Krokidis, H. Toulhoat, JL Le Loarer, JP Jolivet and C. Froidefond. This method makes it possible to obtain alumina, which is commonly called "flash alumina".

[0053] When sodium is present in the alumina support, it is generally introduced during or after the synthesis of the alumina. More particularly, the sodium present in the support may already be present in an aluminum precursor, for example an aluminum hydroxide type precursor. The sodium present in the alumina support may also be introduced in the desired amount into the support during the shaping of the support, for example during the granulation step during the synthesis of flash alumina, or by impregnation of the aluminum precursor.

[0054] Methods for the preparation of catalysts The introduction of the active phase onto the support can be carried out according to any method of preparation known to those skilled in the art. The addition of the active phase to the support consists of contacting at least one component of group VIB, at least one component of group VIII, phosphorus and optionally sodium with the support to obtain a catalyst precursor.

[0055] According to a first mode of implementation, the components of group VIB and group VIII elements, phosphorus and optionally sodium are deposited on the support by one or more co-impregnation steps, i.e. the components of group VIB and group VIII elements, phosphorus and optionally sodium are simultaneously introduced into the support. The co-impregnation step(s) is / are preferentially carried out by dry impregnation or excess impregnation of the solution. If this first embodiment comprises the implementation of several co-impregnation steps, then after each co-impregnation step, preferably, a step of intermediate drying is carried out, which is generally carried out at a temperature below 200° C., advantageously between 50° C. and 180° C., preferably between 60° C. and 150° C., highly preferably between 75° C. and 140° C., for a period generally between 0.5 and 24 hours, preferably between 0.5 and 12 hours.

[0056] According to a preferred embodiment of the co-impregnation, the impregnation solution is preferably an aqueous solution. Preferably, when the impregnation aqueous solution contains cobalt, molybdenum and phosphorus, the impregnation aqueous solution is prepared under pH conditions that promote the formation of heteropolyanions in the solution. For example, the pH of such an aqueous solution is 1-5.

[0057] According to a second embodiment, the catalyst precursor is prepared by successive depositions, in any order, on said support of a component of group VIB, a component of group VIII and phosphorus and optionally sodium. The depositions may be carried out by dry impregnation, by over-impregnation or else by deposition-precipitation, according to methods well known to those skilled in the art. In this second embodiment, the deposition of the components of metals of groups VIB and VIII and phosphorus and optionally sodium may be carried out by several impregnations, with an intermediate drying step being carried out between two successive impregnations at temperatures generally below 200° C., advantageously between 50° C. and 180° C., preferably between 60° C. and 150° C., highly preferably between 75° C. and 140° C., for a period generally between 0.5 and 24 hours, preferably between 0.5 and 12 hours.

[0058] Whatever the mode of deposition of the above elements, phosphorus and optionally sodium, used, the solvent forming part of the composition of the impregnation solution is chosen so as to solubilize the metal precursors of the active phase, for example water or an organic solvent, for example an alcohol.

[0059] Use may be made, by way of example, of sources of molybdenum, of oxides and hydroxides, molybdic acid and its salts, in particular the ammonium salts, such as ammonium molybdate, ammonium heptamolybdate, phosphomolybdic acid (H 3 PMo 12 O 40 ), and its salts, and in some cases silicomolybdic acid (H 4 SiMo 12 O 40 ) and its salts. The source of molybdenum can be any heteropoly compound, for example of the Keggin, defective Keggin, substituted Keggin, Dawson, Anderson or Strandberg type. Use is preferably made of molybdenum trioxide and heteropoly compounds of the Keggin, defective Keggin, substituted Keggin and Strandberg type.

[0060] The tungsten precursors that can be used are also well known to those skilled in the art. For example, among the sources of tungsten, use may be made of oxides and hydroxides, tungstic acid and its salts, in particular the ammonium salts, such as ammonium tungstate or ammonium metatungstate, phosphotungstic acid and its salts, and in some cases tungstosilicic acid (H 4 SiW 12 O 40 ) and its salts. The source of tungsten can also be any heteropoly compound, for example of the Keggin, defective Keggin, substituted Keggin or Dawson type. Use is preferably made of oxides and ammonium salts, for example ammonium metatungstate, or heteropolyanions of the Keggin, defective Keggin or substituted Keggin type.

[0061] Cobalt precursors which may be used are advantageously chosen, for example, from the oxides, hydroxides, hydroxycarbonates, carbonates and nitrates. Preference is given to using cobalt hydroxide and cobalt carbonate.

[0062] Nickel precursors which may be used are advantageously chosen, for example, from the oxides, hydroxides, hydroxycarbonates, carbonates and nitrates. Preference is given to using nickel hydroxide and nickel hydroxycarbonate.

[0063] Phosphorus can advantageously be introduced into the catalyst in various ways at various stages of its preparation. It can be introduced during the shaping of the alumina support or, preferably, after this shaping. It can advantageously be introduced alone or in a mixture with at least one of the metals of groups VIB and VIII. Phosphorus is preferably introduced, completely or partially, in a mixture with precursors of metals from groups VIB and VIII, on the shaped alumina support by dry impregnation of the alumina support with a solution containing precursors of the metals and of phosphorus. A suitable source of phosphorus is orthophosphoric acid H 3 PO 4 However, its salts and esters, such as ammonium phosphate or mixtures thereof, are also suitable. Phosphorus can also be introduced at the same time as the element(s) from group VIB, for example in the form of heteropolyanions of Keggin, defect Keggin, substituted Keggin or Strandberg type.

[0064] In a variant embodiment according to the invention, in which sodium is added during the introduction of the active phase onto the support, sodium can advantageously be introduced into the catalyst in various ways at various stages of its preparation. It can advantageously be introduced alone or in a mixture with at least one of the elements of groups VIB and VIII and phosphorus. Any source of sodium known to those skilled in the art can be used. Preferably, the source of sodium is sodium nitrate, sodium chloride, sodium hydroxide or even sodium sulfate.

[0065] At the end of the step or steps of contacting the support with the elements of groups VIII and VIB, phosphorus and optionally sodium, the precursor of the catalyst is subjected to a drying step, carried out by any technique known to the person skilled in the art, which is advantageously carried out at atmospheric pressure or at reduced pressure. Preferably, this step is carried out at atmospheric pressure. The temperature at which this step is carried out is below 200°C, preferably between 50°C and 180°C, preferably between 60°C and 150°C, highly preferably between 75°C and 140°C.

[0066] The drying step is advantageously carried out in a traversed bed with hot air or any other hot gas. Preferably, when drying is carried out in a traversed bed, the gas used is either air or an inert gas, such as argon or nitrogen. Highly preferably, drying is carried out in the presence of air in a traversed bed.

[0067] Preferably, the drying step has a duration of 30 minutes to 24 hours, preferably 1 hour to 12 hours.

[0068] At the end of the drying step, a dried catalyst is obtained which can be used as a hydrotreating catalyst after an activation step (sulfurization step).

[0069] According to an alternative embodiment, the dried catalyst can be subjected to a subsequent calcination step, for example under air at a temperature of at least 200° C. Calcination is generally carried out at temperatures up to 600° C., preferably between 200° C. and 600° C., particularly preferably between 250° C. and 500° C. Calcination is generally carried out for a period of between 0.5 h and 16 h, preferably between 1 h and 6 h. It is generally carried out under air. Calcination makes it possible, inter alia, to convert the precursors of the elements of groups VIB and VIII into their oxides.

[0070] Prior to its use as a hydrotreating catalyst, it is advantageous to subject the dried or optionally calcined catalyst to a sulfurization step (activation step). This activation step is carried out by methods well known to those skilled in the art, advantageously under a sulfo-reducing atmosphere in the presence of hydrogen and hydrogen sulfide. The hydrogen sulfide can be used directly or can be generated by a sulfurizing agent, for example dimethyl disulfide.

[0071] (Process for hydrodesulfurization of gasoline) The hydrotreating process comprises contacting a sulfur-containing olefinic gasoline fraction with the above-described catalyst and hydrogen under the following conditions: - the temperature is between 200°C and 400°C, preferably between 230°C and 330°C; the total pressure is 1 to 3 MPa, preferably 1.5 to 2.5 MPa; - Hourly space velocity (HSV) is defined as the volumetric flow rate of the feed relative to the volume of the catalyst and is expressed as 1 to 10 h -1 , preferably 2 to 6 hours -1 is; The volume ratio of hydrogen / gasoline feedstock is between 100 and 600 SL / L, preferably between 200 and 400 SL / L.

[0072] The process according to the invention therefore makes it possible to process any type of sulfur-containing olefinic gasoline fraction, such as fractions coming from coking, visbreaking, steam cracking or catalytic cracking (FCC: Fluid Catalytic Cracking) units. This gasoline may possibly consist of a significant proportion of gasoline coming from other production processes, such as atmospheric distillation (gasoline (or straight run gasoline) coming from direct distillation) or conversion processes (coking or steam cracking gasoline). The feedstock preferably consists of a gasoline fraction coming from a catalytic cracking unit.

[0073] The feedstock is advantageously a gasoline fraction containing sulphur-containing compounds and olefins and has a boiling point between 30°C and less than 250°C, preferably between 35°C and 240°C, suitably between 40°C and 220°C.

[0074] The sulfur content of the gasoline fraction produced by catalytic cracking (FCC) depends on the sulfur content of the feedstock processed by FCC, on the presence or absence of pretreatment of the FCC feedstock, as well as on the end point of the fraction. In general, the total sulfur content of gasoline fractions, especially those derived from FCC, is greater than 100 ppm by weight, most often greater than 500 ppm by weight. For gasolines with an end point of greater than 200° C., the sulfur content is often greater than 1000 ppm by weight; in some cases, they can even reach values ​​of the order of 4000-5000 ppm by weight.

[0075] In addition, gasoline coming from a catalytic cracking (FCC) unit contains, on average, 0.5% to 5% by weight of diolefins, 20% to 50% by weight of olefins, and 10 ppm to 0.5% by weight of sulfur, which generally contains less than 300 ppm of thiols. The thiols are generally concentrated in the light fractions of gasoline, more particularly in the fractions with a boiling point below 120° C.

[0076] It should be noted that the sulfur compounds present in gasoline can also include heterocyclic sulfur compounds, such as thiophenes, alkylthiophenes or benzothiophenes. These heterocyclic compounds, unlike thiols, cannot be removed by extraction methods. These sulfur compounds are in turn removed by hydrotreating, which removes their hydrocarbon and H 2 This leads to conversion to S.

[0077] Preferably, the gasoline treated by the method according to the invention is heavy gasoline HCN resulting from a distillation process aimed at separating the broad cut of gasoline resulting from the cracking process (i.e. FRCN for Full Range Cracked Naphtha) into light gasoline (LCN for Light Cracked Naphtha) and heavy gasoline (i.e. HCN for Heavy Cracked Naphtha). The cut points of light and heavy gasoline are determined so as to limit the sulfur content of light gasoline and to allow its use in the gasoline pool, preferably without further post-processing. Advantageously, the broad cut FRCN is subjected to a selective hydrogenation step described below before the distillation step.

[0078] (Example) Example 1: Catalyst A (not in accordance with the invention) 100 grams of TH200® alumina sold by Sasol® are calcined in a fixed traverse bed at 750° C. for 4 hours under an air flow of 1 L / h / g. The support S1 thus obtained has a specific surface area of ​​90 m 2 / g, the pore volume, measured by mercury porosimetry, is 0.60 mL / g, and the loss on ignition is 2.6 wt %.

[0079] Cobalt, molybdenum and phosphorus are then added. The impregnation solution is prepared by dissolving molybdenum oxide (2.25 g, purity ≧99.5%, Sigma-Aldrich®), cobalt hydroxide (0.61 g, purity 99.9%, Alfa Aesar®), 85 wt.% phosphoric acid (0.51 g, purity 99.99%, Sigma-Aldrich®) in 15.6 mL of water at 90° C. After dry impregnation of 20 g of support S1, the impregnated alumina is left to age in a water-saturated atmosphere at ambient temperature for 24 hours and then dried at 120° C. for 16 hours. The dried catalyst thus obtained is designated A.

[0080] The final metal composition of catalyst A, determined by X-ray fluorescence and expressed in oxide form and relative to the weight of the dry catalyst, is as follows: MoO 3 = 10.0 ± 0.2 wt%, CoO = 2.1 ± 0.1 wt%, and P 2 O 5 =1.4±0.1 wt.%. The molar ratios of Co / Mo and P / Mo are 0.40 and 0.28, respectively. The sodium content is determined by ICP and expressed as oxide, relative to the total weight of the catalyst, Na 2 O=0.002±0.001 wt.%. The P / Na molar ratio of catalyst A is 306. The Co / Na and Mo / Na molar ratios are 436 and 1082, respectively.

[0081] Example 2: Catalyst B (not in accordance with the invention) Support S2 is obtained by adding sodium to support S1. The impregnation solution is prepared by dissolving sodium nitrate (0.3 g) in 18.6 mL of water at 90° C. After dry impregnation of 20 grams of support S1, the impregnated alumina is left to age at ambient temperature in a water-saturated atmosphere for 24 hours, then dried at 120° C. for 16 hours and calcined in a fixed transverse bed at 450° C. for 4 hours under an air flow of 1 L / h / g. The support S2 thus obtained has a pore volume, measured by mercury porosimetry, of 0.60 mL / g and an ignition loss of 1.4% by weight.

[0082] Cobalt, molybdenum and phosphorus are then added. The impregnation solution is prepared by dissolving molybdenum oxide (2.28 g, purity ≧99.5%, Sigma-Aldrich®), cobalt hydroxide (0.62 g, purity 99.9%, Alfa Aesar®), 85 wt.% phosphoric acid (0.52 g, purity 99.99%, Sigma-Aldrich®) in 15.6 mL of water at 90° C. After dry impregnation of 20 g of support S2, the impregnated alumina is left to age in a water-saturated atmosphere at ambient temperature for 24 hours and then dried at 120° C. for 16 hours. The dried catalyst thus obtained is designated B.

[0083] The final metal composition of catalyst B, determined by X-ray fluorescence and expressed in oxide form and relative to the weight of the dry catalyst, is as follows: MoO 3 = 10.0 ± 0.2 wt%, CoO = 2.1 ± 0.1 wt%, and P 2 O 5 = 1.4 ± 0.1 wt.%. The molar ratios of Co / Mo and P / Mo are 0.40 and 0.28, respectively. The sodium content is determined by ICP and expressed as oxide, relative to the total weight of the catalyst, and is expressed as Na 2 O=0.45±0.02 wt.%. The P / Na molar ratio of catalyst B is 1.4. The Co / Na and Mo / Na molar ratios are 1.9 and 4.8, respectively.

[0084] Example 3: Catalyst C (not in accordance with the invention) The alumina support S3 supplied by Axens® has a specific surface area of ​​95 m 2 / g, the pore volume, measured by mercury porosimetry, is 0.76 mL / g, and the loss on ignition is 5.0 wt %.

[0085] Cobalt and molybdenum are then added. The impregnation solution is prepared by dissolving ammonium heptamolybdate tetrahydrate (2.71 g, 99.98% purity, Sigma-Aldrich®) and cobalt nitrate hexahydrate (1.80 g, 98% purity, Sigma-Aldrich®) in 15.0 mL of water at 90° C. After dry impregnation of 20 g of support S3, the impregnated alumina is left to age in a water-saturated atmosphere at ambient temperature for 24 hours and then dried at 120° C. for 16 hours. The dried catalyst thus obtained is designated C.

[0086] The final metal composition of catalyst C, determined by X-ray fluorescence and expressed in oxide form and relative to the weight of the dry catalyst, is as follows: MoO 3 %. The molar ratios of Co / Mo and P / Mo are 0.40 and 0, respectively. The sodium content is determined by ICP and expressed as oxide, relative to the total weight of the catalyst, and is expressed as Na 2 O=0.085±0.005 wt.%. The P / Na molar ratio of the catalyst is 0. The Co / Na and Mo / Na molar ratios are 10 and 25, respectively.

[0087] Example 4: Catalyst D (According to the Invention) The catalyst support D is also the support S3. Cobalt, molybdenum and phosphorus are then added. The impregnation solution is prepared by a solution of molybdenum oxide (2.2 g, purity ≧99.5%, Sigma-Aldrich®), cobalt hydroxide (0.60 g, purity 99.9%, Alfa Aesar®), 85% by weight phosphoric acid (0.48 g, purity 99.99%, Sigma-Aldrich®) in 14.9 mL of water at 90° C. After dry impregnation of 20 g of support S3, the impregnated alumina is left to age in a water-saturated atmosphere at ambient temperature for 24 hours and then dried at 120° C. for 16 hours. The dried catalyst thus obtained is designated D.

[0088] The final metal composition of catalyst D, determined by X-ray fluorescence and expressed in oxide form and relative to the weight of the dry catalyst, is as follows: MoO 3 = 10.0 ± 0.2 wt%, CoO = 2.1 ± 0.1 wt%, and P 2 O 5 = 1.4 ± 0.1 wt.%. The molar ratios of Co / Mo and P / Mo are 0.40 and 0.28, respectively. The sodium content is determined by ICP and expressed as oxide, relative to the total weight of the catalyst, and is expressed as Na 2 O=0.084±0.005 wt.%. The P / Na molar ratio of the catalyst is 7.3. The Co / Na and Mo / Na molar ratios are 10 and 26, respectively.

[0089] (Example 5: Evaluation of the performance of catalysts A to D used in a hydrodesulfurization reactor) In this example, the performance of catalysts A to D is evaluated in the hydrodesulfurization of catalytically cracked gasoline.

[0090] A model feedstock representative of catalytic cracking (FCC) gasoline containing 10 wt% 2,3-dimethylbut-2-ene and 0.33 wt% 3-methylthiophene (i.e., 1000 wt ppm sulfur in the feedstock) is used to evaluate the catalytic performance of various catalysts. The solvent used is heptane.

[0091] The hydrodesulfurization (HDS) reaction was carried out in a fixed-type cross-bed reactor at 210°C, HSV=6h under a total pressure of 1.5MPa. -1 (HSV = volumetric flow rate of feedstock / volume of catalyst) and H 2 The reaction is carried out in the presence of 4 mL of catalyst at a volume ratio of 300 SL / L of feedstock. Prior to the HDS reaction, the catalyst was sulfided in situ with 15 mol% H at 350° C. for 2 h. 2 The reaction is carried out under a stream of S-containing hydrogen at atmospheric pressure.

[0092] Each of the catalysts is placed successively in the reactor. At different time intervals, samples are taken and analyzed by gas chromatography to observe the disappearance of reactants and the formation of products.

[0093] The catalytic performance of the catalysts is evaluated in terms of catalytic activity and selectivity. The hydrodesulfurization (HDS) activity is expressed as the rate constant (kHDS) for the HDS reaction of 3-methylthiophene normalized by the volume of catalyst introduced, assuming first-order reaction kinetics for sulfur-containing compounds. The olefin hydrogenation (HydO) activity is expressed as the rate constant for the hydrogenation reaction of 2,3-dimethylbut-2-ene normalized by the volume of catalyst introduced, assuming first-order reaction kinetics for olefins.

[0094] The selectivity of the catalyst is expressed by the normalized ratio of the rate constants kHDS / kHydO. The kHDS / kHydO ratio will increase as the catalyst becomes more selective. The obtained values ​​are normalized by taking catalyst A as the reference (relative HDS activity and relative selectivity equal to 100). The performance qualities are therefore the relative HDS activity and relative selectivity. The results are listed in Table 1 below.

[0095] [Table 1]

[0096] Therefore, it is found that the catalyst D according to the present invention shows better performance in terms of activity and selectivity compared to the unsuitable catalysts A, B and C, and therefore the adjusted Na content in the catalyst is useful for obtaining improved performance in the gasoline hydrodesulfurization process. 2 The importance of the O content and the specific optimized P / Na molar ratio is emphasized. This improvement in the selectivity of the catalyst is particularly advantageous in the case of its use in a process for hydrodesulfurization of gasoline containing olefins, in which it is desired to limit as much as possible the loss of octane due to the hydrogenation of the olefins.

Claims

1. A catalyst comprising at least one Group VIB element, at least one Group VIII element, phosphorus, sodium, and a support comprising alumina, wherein the sodium content is Na 2 50-2000 ppm by weight of sodium, measured in the form of O-oxide, relative to the total weight of said catalyst, and the molar ratio between phosphorus and sodium, calculated on the basis of the phosphorus content and the sodium content, relative to the total weight of the catalyst, is 1.5-300.

2. Catalyst according to claim 1, characterized in that the total content of group VIII elements is between 0.5 and 10% by weight, expressed as the weight of the oxides of said group VIII elements relative to the total weight of the catalyst.

3. Catalyst according to claim 1 or 2, characterized in that the content of group VIB element is between 1 and 30% by weight, expressed as the weight of the oxide of said group VIB element relative to the total weight of the catalyst.

4. The phosphorus content is the phosphorus content relative to the total weight of the catalyst. 2 O 5 2. The catalyst according to claim 1, wherein the weight of the catalyst is 0.1 to 10% by weight.

5. 2. The catalyst according to claim 1, characterized in that the molar ratio between the group VIII element and the group VIB element is between 0.1 and 0.

8.

6. 2. The catalyst according to claim 1, characterized in that the molar ratio between the group VIII element and the sodium is between 2 and 400, calculated on the basis of the content of the group VIII element and the sodium content relative to the total weight of the catalyst.

7. 2. The catalyst according to claim 1, characterized in that the molar ratio between the group VIB element and the sodium is between 5 and 500, calculated on the basis of the content of the group VIB element and the sodium content relative to the total weight of the catalyst.

8. 2. The catalyst according to claim 1, characterized in that the molar ratio between phosphorus and group VIB element is between 0.2 and 0.

35.

9. The phosphorus content is the phosphorus content relative to the total weight of the catalyst. 2 O 5 2. The catalyst according to claim 1, characterized in that the amount of the catalyst is 0.3 to 5% by weight.

10. Catalyst according to claim 1, characterized in that the molar ratio between phosphorus and sodium is between 2 and 100, calculated on the basis of the phosphorus content and the sodium content relative to the total weight of the catalyst.

11. 2. The catalyst of claim 1, wherein the group VIII element is cobalt and the group VIB element is molybdenum.

12. The specific surface area of ​​the catalyst is 50 m 2 / g to 200m 2 The catalyst according to claim 1, characterized in that the Mo content is 1 / g.

13. The pore volume of the catalyst is 0.5 cm 3 / g ~ 1.3 cm 3 The catalyst according to claim 1, characterized in that the Mo content is 1 / g.

14. A process for hydrodesulfurization of a sulfur-containing olefinic gasoline fraction, comprising contacting the gasoline fraction, hydrogen and the catalyst according to claim 1, the hydrodesulfurization process being carried out at a temperature of 200° C. to 400° C., a total pressure of 1 to 3 MPa, and an hourly space velocity, defined as the volumetric flow rate of the feed relative to the volume of the catalyst, of 1 h. -1 ~10h -1 and the volume ratio of hydrogen / gasoline fraction is 100-600 SL / L.

15. 15. The method of claim 14, wherein the gasoline is gasoline produced from a catalytic cracking unit.